TANTANGAN PENDIDIKAN SEKOLAH DASAR MASA DEPAN - Rizki Ananda; Lusi Gita Karlina; Dita Amanda; Nurul Syafira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Using a descriptive qualitative literature study, this research aims to find and analyze the problems facing primary school education in the future.  The research focuses on two main elements: challenges to implementing learning technology and issues of teacher quality and welfare. The analysis shows that the major barriers to implementing technology-based learning are the gap in access to technology infrastructure and the low level of digital literacy in some areas.  In contrast, the quality of learning depends heavily on teacher preparedness. Lack of professional training and lack of welfare can reduce teacher motivation and performance.  Therefore, to face the challenges of basic education in the future, a concerted effort is needed to ensure everyone has access to technology, improve their capacity and sustainably safeguard teachers' welfare. These results are expected to contribute to the formation of flexible and inclusive education policies in the digital and global era.